Análise evolutiva das características do eletrocardiograma e do ecocardiograma na doença de chagas - GUSMÃO, Flávia Ataíde (2020)
Chagas disease belongs to the thirteen most neglected tropical diseases in the world, occupying the third position in relation to death rates. The Amazon, which has always been an area of low risk for transmission of Chagas' disease, has shown an increase in the number of cases. The clinical picture of the acute phase can present several manifestations, such as fever, subcutaneous edema, anemia, lymph node enlargement, hepatomegaly, splenomegaly, megaesophagus and megacolon, besides myocarditis, as well as oligosymptomatic forms. In most cases, acute myocarditis begins between 15 to 20 days of disease. The main signs and symptoms are dyspnoea, palpitations, tachycardia and, eventually, precordial pains, mimicking myocardial infarction. Myocarditis is one of the most frequent complications, and electrocardiographic and echocardiographic examinations should be performed immediately after diagnosis and during the short term, in the search for signs of cardiac compromise, given the transience of some manifestations. The present study aims to analyze the evolutionary behavior of the variables of the electrocardiogram and the ventricular function in an two year period after the initial infection, using a series case observational study, carried out at the Hospital Universitário João de Barros Barreto (HUJBB). For population analysis, medical charts of outpatients and hospitalized patients from different age groups were studied in 2006 to 2013 by two cardiology specialists and blinded for the study. The N of the study was 58 patients and the inclusion criteria refer to positive parasitological examination for acute Chagas' disease, excluding incomplete medical records. Thus, a similar prevalence was found between the genders, each with 29 individuals (50%), the majority with a mean age of 40 years, coming from the interior of Para. Electrocardiographic changes demonstrated a decrease in heart rate (HR) over time. This was because the mean HR in the acute phase of the disease (T = 0) consisted of 77 bpm, declining significantly to 70 bpm after 2 years of the acute phase (T = 2), P-value = 0.019. In relation to the change in PR interval, PR space, duration of QRS and QTC over time, the statistical results showed no changes (P-value> 0.05). In the qualitative aspect, the analysis of the T wave, supraventricular arrhythmias, ventricular arrhythmias and axis, did not observe significant alterations that were maintained during the analysis. Regarding the echocardiogram, the following parameters were evaluated: systolic, diastolic, interventricular septum, posterior wall, left atrial size and ejection fraction, but did not show significant variation over time (P-value> 0, 05). Therefore, it was observed that the significant finding was the decrease in HR after two years of the acute phase and, later, that the changes of the ventricular repolarization persisted from the acute phase to the period of two years in 4 patients and, until the end of the 2nd year of analysis, in 3 patients, but did not correlate with the ventricular function on the echocardiogram, which was normal, demonstrating that the electrocardiogram is the most sensitive clinical marker for the evolutionary analysis of the patient group.